Tradisi Mohataman Al-Qur’an Bulan Ramadhan dalam Menyambut Lebaran di Kampung Pos Sentul (Studi Living Hadis) - Melisa Nur Azizah; Muhammad Alif (Moral : Jurnal kajian Pendidikan Islam, 2025)
The tradition of mohataman Al-Qur'an is one of the religious practices that is alive and thriving among Indonesian Muslims, especially during Ramadan in preparation for Eid al-Fitr. In Kampung Pos Sentul, this tradition is carried out collectively by the community as a form of gratitude for the completion of fasting and as a means of strengthening Islamic brotherhood. This study aims to examine the tradition of mohataman Al-Qur'an from the perspective of living hadith, which is to see how the hadith of the Prophet Muhammad is understood, internalized, and manifested in the social-religious practices of the community. The research method used is qualitative with a descriptive approach, through observation, interviews, and documentation. The results of the study show that the tradition of mohataman Al-Qur'an is based on the community's understanding of the hadiths about the virtues of reading the Qur'an, the encouragement to increase acts of worship during Ramadan, and the importance of togetherness in doing good. This tradition is not only ritualistic in nature, but also has social, educational, and spiritual dimensions that strengthen the religious identity of the Pos Sentul Village community. Thus, mohataman Al-Qur'an can be understood as a form of actualization of hadith in real life that continues to live on and is passed down from generation to generation.